Metode Design Thinking UI/UX Aplikasi UMKM Sanfresh - Rita Komalasari; Riksania Helga Tsalitsa; Zen Munawar; Novianti Indah Putri (Jurnal ICT: Information Communication & Technology, 2023)
Switching to online media is one of the solutions for MSME players to survive during the pandemic at that time, one of which is Sanfresh MSMEs engaged in e-commerce for fresh vegetable and fruit products, even during the Covid-19 pandemic e-commerce is projected to continue to grow, in terms of any business it is to offer a pleasant and useful experience for customers. This research aims to create User interface and User experience of Sanfresh MSME mobile-based applications using the Design thinking method. User interface and user experience of Sanfresh MSME mobile-based applications are expected to be the beginning of a good step to produce an attractive appearance of the application and produce a good experience for users when visiting the application, because that is the most important thing before developing an application.